Orang Tua Sebagai Supporting System: Penanganan Anak Remaja Yang Mengalami Depresi - Eva Oktavia Soumokil-Mailoa; Yanto Paulus Hermanto; Juliana Hindradjat (Vox Dei: Jurnal Teologi dan Pastoral, 2022)
Adolescence is a period of searching for identity in a life process. Not a few teenagers who do exploratory actions in this phase. These actions can affect changes physically, psychologically and psychosocially. Not infrequently the actions taken or obtained by a teenager lead the teenager to psychiatric and mental disorders such as depression. It is known that no less than one third of teenagers in Indonesia are teenagers with depressive disorders. In such conditions, parents as the first environment of a teenager have an important role to improve the mental health and psyche of a teenager. This study aims to look at the role of parents as a supporting system in dealing with depressed adolescents. The method used in this research is descriptive qualitative with a literature study approach. The data used is secondary data obtained by observing the literature. The results showed that (1) depression is a psychiatric disorder that is prone to occur in adolescents. Depression is also related to the lifestyle of adolescents, age, gender, socio-economic conditions, and the existence of acts of bullying that have been received by these adolescents; (2) depression can affect the psychological and social well-being of a teenager. Therefore, parents must have an understanding of the indications and causes of depression so that parents are able to take appropriate action and can become a support system for a teenager who is experiencing depression; (3) high support from parents can provide a greater opportunity for adolescents to get out of depression.